Forecast the Processes of Thawing of Permafrost Soils under the Building with the Large Heat Emission - Paramonov Vladimir; Sakharov Igor; Kudriavtcev Sergey (MATEC Web of Conferences, 2016)
The paper describes a mathematical model of the soil experiencing freezing and thawing. The mathematical model is realized by the authors with the use of finite element method in the program «Termoground». The results of calculation the processes of the thawing of permafrost soil under the building with the large heat emission with various constructive measures for the conservation of frozen soil structure are given. Taking into account high costs of such measures it is recommended a combination of I and II principles of the design of foundations allowing partial thawing of soil, which requires the ability to predict the deformation of thawing soil.